IL‐17 serum level in patients with chronic mucocutaneous candidiasis disease. (25th January 2022) - Chimenz, Roberto; Tropeano, Angelo; Chirico, Valeria; Ceravolo, Giorgia; Salpietro, Carmelo; Cuppari, Caterina
Abstract: Background: Chronic mucocutaneous candidiasis (CMC) is defined by recurrent or persistent superficial infections involving nails, skin, and/or oral and genital mucosae. IL‐17 promotes the recruitment, chemotaxis, and expansion of neutrophils and acts directly on keratinocytes and epithelial cells, driving the production of antimicrobial peptides, essential for the immune response against Candida. Aim: To evaluate the serum level of IL‐17 in a family affected by CMC restricted to the nails of the hands and feet. Methods: Serum IL‐17 was assayed on 16 patients (aged 21 ± 3.1 years) suffering from persistent onychomycosis caused by Candida and 18 healthy controls (aged 19 ± 2.7 years). Comparisons between groups were performed by Student's unpaired t ‐test. The level of significance was set at 0.05. Results: The mean serum IL‐17 level in patients was 74 ± 1.42 pg/ml, whereas the control group showed a significantly lower level of 25.6 ± 6.7 pg/ml ( p  < 0.05). Conclusions: We showed a potential defect in the IL‐17 signaling pathway in a family affected by CMC restricted to the nails of the hands and feet. Further research is needed to clarify the immunological mechanisms and the genetic etiology at the basis of the unusual clinical presentation in this family.